Learning adaptive regularization for image labeling using geometric assignment - Hühnerbein, Ruben; Savarino, Fabrizio; Petra, Stefania; Schnörr, Christoph (Journal of mathematical imaging and vision, 2021)
We study the inverse problem of model parameter learning for pixelwise image labeling, using the linear assignment flow and training data with ground truth. This is accomplished by a Riemannian gradient flow on the manifold of parameters that determines the regularization properties of the assignment flow. Using the symplectic partitioned Runge-Kutta method for numerical integration, it is shown that deriving the sensitivity conditions of the parameter learning problem and its discretization commute. A convenient property of our approach is that learning is based on exact inference. Carefully designed experiments demonstrate the performance of our approach, the expressiveness of the mathematical model as well as its limitations, from the viewpoint of statistical learning and optimal control.
Published online: 6 August 2020
Gesehen am 04.10.2021